Implementation of the School Curriculum to Empower Education in the Digital Era 4.0 for Quality Human Resources - Febriani Dwi Sari; Rugaiyah Rugaiyah (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The development of the digitalization era cannot be avoided. The development of science in various fields, mainly Information and Communication Technology (ICT), is rapidly increasing. An educator needs to update and introduce students to be more technology literate. One is implementing a curriculum that empowers education in the digital era 4.0. This research aims to provide an understanding that the right curriculum for students will produce quality human resources in the era of globalization. Method: This research uses a qualitative approach with a literature study or literature review method. Data was collected by reviewing official sites such as Google Scholar, Research Gate, Public and Perish, and Sinta. Result: The results showed that implementing a curriculum relevant to the demands of the times is a must. The curriculum must reflect learners' needs and create creative, innovative, and competitive individuals. Novelty: This research offers new insight into implementing a school curriculum that supports enhancing students' digitalization capabilities in the Industry 4.0 era. In addition, this research also explores how curriculum can play a role in creating quality human resources. This research recommends that education should continue to be sensitive to the times and implement the curriculum according to the needs of current and future learners.